Time-resolved high-resolution spectroscopy of the pulsating sdB star QQ Vir (PG1325+101) - Telting, J.; Ostensen, R.; Oreiro, R.; Heber, Ulrich; Vuckovic, Maja; Randall, S.; Baran, Andrzej (Astrophysics and Space Science, 2010)
In March 2008 we obtained 2 nights of time-resolved high-resolution spectroscopy with UVES@VLT of the pulsating sdB QQ Vir (PG1325+101), totalling more than 750 spectra. We aim to study in detail the atmospheric response to the pulsations, and to derive observational constraints on the eigenmode of the main pulsation. In this paper we present the first preliminary results.We follow the technique outlined in Telting et al. (Astron. Astrophys. 492:815, 2008) in order to obtain high-quality line-profile variations from phase-folded spectra. From the modelling of such line-profile variations we aim to derive constraints on the pulsational degree a"" and azimuthal number m of the main pulsation mode in this star.To facilitate accurate frequency determination of the pulsations in QQ Vir, and to strengthen the derivation of the degree a"" of the main mode, we organised a photometric campaign around the spectroscopic observations. This photometric campaign will be discussed in a separate contribution (Baran et al. in Astrophys. Space Sci. 2010, this volume).
Keywords: Stellar pulsations; Subdarf B stars; QQ Vir (PG1325+101); Pulsation-mode identification; Time-resolved spectroscopy; Internal stellar structure; Stellar evolution